Effect of sun exposure versus oral vitamin D supplementation on serum 25-hydroxyvitamin D concentrations in young adults: A randomized clinical trial. Issue 3 (March 2020) - Joh, Hee-Kyung; Hwang, Seung-sik; Cho, BeLong; Lim, Chun Soo; Jung, Sung-Eun
Summary: Background: Vitamin D inadequacy is associated with a wide range of diseases. However, optimal strategies to improve vitamin D status, especially in Asian populations, remain unclear. We tested the hypotheses that (1) relevant sun exposure or oral vitamin D supplementation would significantly increase serum 25-hydroxyvitamin D (25OHD) concentrations compared with placebo, (2) sun exposure and supplementary vitamin D would be similar in serum 25OHD increases, and (3) the two interventions may have different effects on cardio-metabolic markers. Methods: In this 8-week randomized placebo-controlled clinical trial including vitamin D-deficient adults in Seoul (37 °N), Korea, changes in serum 25OHD concentrations were compared between the sun exposure (daily ≥20–30 min around noon, n  = 50), oral vitamin D3 (500 IU/d, n  = 50), and control (placebo, n  = 50) groups. Results: Both sun exposure and oral vitamin D3 effectively increased serum 25OHD concentrations. Compared with placebo, the between-group least-squares mean (LSM) differences in changes were 2.2 ng/mL (95% CI: 0.2, 4.2) in the sun exposure group and 8.5 ng/mL (6.5, 10.5) in the oral vitamin D3 group. Increases in serum 25OHD were greater with oral vitamin D3 than with sun exposure (LSM difference in changes = 6.3 ng/mL, 95% CI: 4.3, 8.3). More participants in the oral vitamin D3 group (54.2%) achieved serum 25OHD concentrations ≥20 ng/mL at week 8 than those in the sun exposure (12.2%) or control (4.3%) groups. Compliance with sun exposure advice was relatively low, and only those with adequate compliance had a significant increase in serum 25OHD. Changes in the cardio-metabolic markers were mostly insignificant in all groups. Conclusions: Enhanced sun exposure and 500 IU/d of oral vitamin D3 supplementation significantly increased serum 25OHD concentrations. However, our protocol for sun exposure was not as effective as 500 IU/d of oral vitamin D3 supplementation. This trial was registered at clinicaltrials.gov as NCT03310242 . Graphical abstract: Image 1 Highlights: Optimal strategies to improve vitamin D status in Asian populations remain unclear. Enhanced sun exposure (≥20–30 min/d around noon) and 500 IU/d oral vitamin D3 significantly increased serum 25OHD levels. The mean increase of serum 25OHD concentrations was greater with oral vitamin D3 supplementation than sun exposure. Compliance to sun exposure advice was relatively low in Korean young adults. Little benefits on cardio-metabolic markers were found with either sun exposure or oral vitamin D3 supplementation.